2017
DOI: 10.48550/arxiv.1702.04674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Almost global existence of solutions for capillarity-gravity water waves equations with periodic spatial boundary conditions

Massimiliano Berti,
Jean-Marc Delort

Abstract: 1 partially supported by PRIN 2012 "Variational and perturbative aspects of nonlinear differential problems".2 partially supported by the ANR project 13-BS01-0010-02 "Analyse asymptotique des équations aux dérivées partielles d'évolution".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(57 citation statements)
references
References 56 publications
1
56
0
Order By: Relevance
“…In particular, if ω 0 = 0, this gives a proof that the solution can be continued until T ∼ ε −N 0 . See also [20] for a similar lifespan bound for irrotational water waves on a periodic domain. Let us make a few remarks.…”
Section: Introductionmentioning
confidence: 91%
“…In particular, if ω 0 = 0, this gives a proof that the solution can be continued until T ∼ ε −N 0 . See also [20] for a similar lifespan bound for irrotational water waves on a periodic domain. Let us make a few remarks.…”
Section: Introductionmentioning
confidence: 91%
“…A new different approach in the case of super-linear dispersion law (i.e. L has order > 1) has been proposed by Berti-Delort in [7] for the capillary water waves equation. The starting point is to rewrite the equation as a para-differential system which involves a para-differential term and a smoothing remainder.…”
Section: Introductionmentioning
confidence: 99%
“…For more details on this strategy we refer the reader to the introduction of [7]. We mention that in [18], [17] it has been shown that a large class of fully non linear Schrödinger type equations admits quasi-periodic in time, and hence globally defined and stable, small amplitude solutions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations